2011
DOI: 10.1074/jbc.m111.229781
|View full text |Cite
|
Sign up to set email alerts
|

5′-Methylthioadenosine Nucleosidase Is Implicated in Playing a Key Role in a Modified Futalosine Pathway for Menaquinone Biosynthesis in Campylobacter jejuni

Abstract: Menaquinone (vitamin K 2 ) serves as an electron carrier in the electron transport chain required for respiration in many pathogenic bacteria. Most bacteria utilize a common menaquinone biosynthetic pathway as exemplified by Escherichia coli. Recently, a novel biosynthetic pathway, the futalosine pathway, was discovered in Streptomyces. Bioinformatic analysis strongly suggests that this pathway is also operative in the human pathogens Campylobacter jejuni and Helicobacter pylori. Here, we provide compelling ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 44 publications
1
57
0
Order By: Relevance
“…A report in 2008 indicated that several bacterial species do not possess homologues of men B to men F and thus must encode a distinct pathway for menaquinone biosynthesis. 10 Subsequent genetic and biochemical analysis indicated an alternative menaquinone synthetic pathway involving the mqn genes with deoxyfutalosine or 6-amino-6-deoxyfutalosine as intermediates (Figure 7) 11,12 . These intermediates are processed by a purine nucleoside hydrolase with homology to other bacterial 5′-methylthioadenosine nucleosidases (MTANs).…”
Section: Bacterial Menaquinone Synthesis: the Futalosine Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…A report in 2008 indicated that several bacterial species do not possess homologues of men B to men F and thus must encode a distinct pathway for menaquinone biosynthesis. 10 Subsequent genetic and biochemical analysis indicated an alternative menaquinone synthetic pathway involving the mqn genes with deoxyfutalosine or 6-amino-6-deoxyfutalosine as intermediates (Figure 7) 11,12 . These intermediates are processed by a purine nucleoside hydrolase with homology to other bacterial 5′-methylthioadenosine nucleosidases (MTANs).…”
Section: Bacterial Menaquinone Synthesis: the Futalosine Pathwaymentioning
confidence: 99%
“…These intermediates are processed by a purine nucleoside hydrolase with homology to other bacterial 5′-methylthioadenosine nucleosidases (MTANs). 11,45 Tansition state analogue design work on pathways of quorum sensing in Gram-negative bacteria had already targeted MTAN to produce powerful inhibitors with dissociation constants as low as 47 fM. 4648 These were immediate candidates for the H. pylori MTAN.…”
Section: Bacterial Menaquinone Synthesis: the Futalosine Pathwaymentioning
confidence: 99%
“…5¢-Methylthioadenosine/S-adenosylhomocysteine nucleosidase (pfs) enzyme catalyzes the direct conversion of aminodeoxyfutalosine (AFL) into dehypoxanthine futalosine (DHFL) and adenine via the hydrolysis of the N-glycosidic bond that represents an essential step in the menaquinone biosynthesis pathway (Li et al, 2011). This enzyme is an attractive drug target as it is involved in many pathways, such as ubiquinone and other terpenoid-quinone biosynthesis, cysteine and methionine metabolism, and biosynthesis of amino acids.…”
Section: Discussionmentioning
confidence: 99%
“…37,38 MTANs from E. coli and Vibrio cholera are closely related in catalytic properties and catalytic site structure. Yet, transition state analogues bind several orders of magnitude more tightly to the enzyme from E. coli .…”
Section: Dynamic Significance Of Thermodynamics In Transition Smentioning
confidence: 99%